Price Spread in Marketing of Coconut in Tamil Nadu - Namasivayam, N.; Richard Paul, V. (Indian Journal of Marketing, 2006)
To find out the price spread of the coconut marketing system in Tamil Nadu, a study wasconducted among the randomly selected 50 coconut intermediaries in Theni District. From thedata obtained, the price spread of coconut, channels of distribution were analysed in the studyarea. In order to see a best channel Shepherd's market efficiency index was used and the study showed that the channel III is the best one.